2003
DOI: 10.2136/sssaj2003.1533
|View full text |Cite
|
Sign up to set email alerts
|

Cropping Intensity Enhances Soil Organic Carbon and Nitrogen in a No‐Till Agroecosystem

Abstract: Soil organic C (SOC) has decreased under cultivated wheat (Triticum aestivum)‐fallow (WF) in the central Great Plains. We evaluated the effect of no‐till systems of WF, wheat–corn (Zea Mays)‐fallow (WCF), wheat–corn–millet (Panicum miliaceum)‐fallow, continuous cropping (CC) without monoculture, and perennial grass (G) on SOC and total N (TN) levels after 12 yr at three eastern Colorado locations. Locations have long‐term precipitation averages of 420 mm but increase in potential evapotranspiration (PET) going… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
142
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(146 citation statements)
references
References 23 publications
3
142
1
Order By: Relevance
“…Combining site data could confound the C saturation analysis if C input level (I) co-varied with decomposition rate (k), resulting in an apparent saturation response of less SOC accumulation at high input levels because of faster decomposition rates due to optimal temperature and moisture conditions. We Sherrod et al 2003 Topographic location…”
Section: Resultsmentioning
confidence: 99%
“…Combining site data could confound the C saturation analysis if C input level (I) co-varied with decomposition rate (k), resulting in an apparent saturation response of less SOC accumulation at high input levels because of faster decomposition rates due to optimal temperature and moisture conditions. We Sherrod et al 2003 Topographic location…”
Section: Resultsmentioning
confidence: 99%
“…This is because the crop biomass yields and C inputs are often lower in drylands than in the humid regions due to limited precipitation and a shorter growing season. As a result, it often takes more time to enrich SOC (Halvorson et al, 2002a;Sherrod et al, 2003). Many studies have identified the potential of soils cultivated with different conservation practices (e.g., no-till) to sequester large amounts of carbon (C).…”
Section: Sequestrationmentioning
confidence: 99%
“…Improved soil and crop management practices, such as reduced tillage and increased cropping intensity, however, would increase SOC as compared to conventional practices (Halvorson et al, 2002a;Sherrod et al, 2003;Sainju et al, 2007). Many studies have reported that implementation of minimum tillage has occasionally caused yield losses, especially in the no tillage method (Rao, 1996;Kirkegaard et al, 1995;Silgram and Shepherd, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In the central Great Plains of the United States, Sherrod et al (2003) evaluated the effects of cropping frequency on SOC stocks over a 12-yr period. At three locations differing in potential evapotranspiration (PET), they situated sampling locations at summit, sideslope and toeslope positions.…”
Section: Representation Of Landscapementioning
confidence: 99%